Exploring the potential use of video in increasing learners’ understanding and motivation / Wan Noorli Razali, Che Haslina Abdullah and Tengku Muhaini Tuan Mat - Razali, Wan Noorli; Abdullah, Che Haslina; Tuan Mat, Tengku Muhaini (2011)
Lecture has always been the only preference of many Islamic Studies Courses’ teachers and lecturers when the generation of students nowadays are exposed to the multimodality of learning process. Many experts strongly believe with solid technology infrastructures, effective and meaningful ICT integration in the lecture rooms is achievable (Vrasidas and Glass, 2005; Grabe, 2004; Tomei, 2002). The findings will be able to help lecturers in making the decision to incorporate video in the religious subjects. This study therefore seeks to explore if video has the potential in assisting the lecturers to maintain students’ focus and increase their understanding and motivation. It is a case study where it adopts the triangulation of qualitative and quantitative research methods. Triangulation of these different data collection methods allows deeper analyses of the findings: test, observation checklist and questionnaire. The findings will then be reported quantitatively as well as qualitatively. Thus, this study will be valuable in helping the lecturers to evaluate the incorporation of technology like video in enhancing students’ understanding and increase their motivation.